Root and Root Canal Morphology: Study Methods and Classifications - Shihab , Duaa M; Mahdee , Anas F (Journal of Baghdad College of Dentistry, 2021)
Background: Morphology of the root canal system is divergent and unpredictable, and rather linked to clinical complications, which directly affect the treatment outcome. This objective necessitates continuous informative update of the effective clinical and laboratory methods for identifying this anatomy, and classification systems suitable for communication and interpretation in different situations. Data: Only electronic published papers were searched within this review. Sources: “PubMed” website was the only source used to search for data by using the following keywords "root", "canal", "morphology", "classification". Study selection: 153 most relevant papers to the topic were selected, especially the original articles and review papers, from 1970 till the 28th of July 2021. Conclusions: This review divided the root canal analysis methods into two approaches; clinical and in vitro techniques. The latter has shown more precise non-subjective readings, on the other hand; the clinical methods provide direct chair side diagnosis for the clinical cases. The classification systems reviewed in the present study, started with the oldest trials that simply presented the root canal systems, according to the degree of angulation, or by coded Latin numbers or English letters. Then, the most recent systems were also presented that were persisted with continuous editions up to date. These new systems could briefly describe the root and root canal’s internal and external details in a small formulation, without confusion and in an easily communicated manner, highly recommended specially for students, teachers, and researchers